Constituent of extracellular polymeric substances (EPS) produced by a range of soil bacteria and fungi - Rebeca Leme Oliva; Umesh B. Khadka; Tessa Camenzind; Jens Dyckmans; Rainer Georg Joergensen (BMC Microbiology)
Abstract Extracellular polymeric substances (EPS) produced by soil bacteria and fungi are crucial for microbial growth and provide many functions for the soil and its microbes. EPS composition may depend on microbial community composition and the soil physical and chemical environment, nevertheless, not much is known about the EPS constituents’ specific roles nor how they interact to alter biofilm’s functions. We hypothesized that EPS production would be enhanced with the presence of a surface and with a more labile carbon source. Also, that even though carbohydrates and proteins are the main constituents of EPS, we could still find quantifiable amounts of mannosamine and galactosamine (two amino sugars previously shown to be part of microbial biofilms). Ten soil bacterial and ten soil fungal species were cultured with glycerol or starch and with or without a quartz matrix. After a 4-day cultivation, EPS were extracted, and seven constituents were determined: carbohydrates, DNA, proteins, muramic acid, mannosamine, galactosamine, and glucosamine. We found EPS composition was strongly modified by microbial type, whereas differences in EPS production were driven mostly by environmental conditions. The EPS-carbohydrate/protein ratio was higher for cultures grown in starch media than in glycerol and increased in the presence of quartz. EPS-carbohydrate concentration reflected environmental changes of substrate quality and surface presence. Contrastingly, changes in the other EPS constituent composition are likely due to intrinsic microbial characteristics. Our findings open the pathway to study microbial biofilms in more complex environments (such as soils) and shed light to the importance of extracellular structures to microbial processes.